Existence of multiple radial solutions for nonlinear equation involving the mean curvature operator in the Lorentz-Minkowski space
We prove the existence of multiple radial solutions for a class of nonlinear equations - involving the mean curvature operator in the Lorentz-Minkowski space - of the form equation* -( abla u1 - abla u^2 ) = λ b(x)u^q-2u + f(x, u) in B_R, equation* with Dirichlet boundary conditions in case q (1,2) and f(x, s) is superlinear in s. Solutions are found using Szulkin’s critical point theory for non-smooth functionals. Multiplicity results are also given for some cases in which f depends also on (the norm of) the gradient of u., journal=Topological Methods in Nonlinear Analysis, author=Coti Zelati, Vittorio and Dong, Xu and Wei, Yuanhong, year=2026, month=Mar., pages=1–33